Artificial Intelligence-Based Learning Environment in Learning Islamic Religious Education in Higher Education : Opportunities and Challenges - Ofiani, Oktawini; Hidayat, Husni; Khalilurrahman, Khalilurrahman; Istan, Muhammad; Apriani, Eka (Corolla International Conference, 2024)
This research aims to explore and analyze the application of Artificial Intelligence (AI)-based learning environments in Islamic education in higher education, as well as identifying the opportunities and challenges faced. In this digital era, the integration of AI in the educational process is expected to improve the quality of learning, personalization of materials and teaching efficiency. This study uses a qualitative method with a case study approach at two private Islamic Religious Universities in Jambi Province which have implemented AI technology in their curriculum. The research results show that the application of AI in Islamic Education learning environment offers a variety of significant opportunities, such as increased access to a wider range of learning resources, the ability to personalize the learning experience for each student, and increased efficiency of administrative processes. However, this research also revealed several key challenges, including limited technological infrastructure, the need for special training for lecturers and teaching staff, and ethical issues related to data privacy and surveillance. The next thing that is in the spotlight as a form of challenge in creating an AI-based learning environment is strengthening collaboration between educational institutions, industry, technology and government for quality education. The main conclusion of this research is that although there are challenges that need to be overcome, the potential benefits offered by AI in Islamic education are enormous and promising. Therefore, it is important for Islamic educational institutions, especially universities, to develop effective and sustainable implementation strategies, including investment in technological infrastructure and training for educators. This research contributes to the existing literature by providing empirical data on the application of AI in Islamic Education and providing practical recommendations for optimizing the use of AI in improving the quality of education in higher education.